HO-1/BVR-a system analysis in plasma from probable Alzheimer's disease and mild cognitive impairment subjects: a potential biochemical marker for the prediction of the disease - Di Domenico, Fabio; Barone, Eugenio; Mancuso, Cesare; Perluigi, Marzia; Cocciolo, Annalisa; Mecocci, Patrizia; Butterfield, D Allan; Coccia, Raffaella (Journal of Alzheimer's disease, 2012)
Several studies showed increased oxidative and nitrosative stress in plasma from patients with Alzheimer's disease (AD), however, little and controversial knowledge has emerged about the antioxidant functionality of the heme oxygenase-1/biliverdin reductase-A (HO-1/BVR-A) system in blood. The current study reports increased levels of both HO-1 and BVR-A in plasma from probable AD patients, as a result of the increased oxidative environment. However, the increase of oxidative stress in plasma result also in the increase of BVR-A 3-nitrotyrosine levels and the decrease of BVR-A phosphotyrosine levels and reductase activity, suggesting that nitrosative stress play the prominent oxidative role in plasma during AD. Our data on HO-1/BVR-A status in plasma closely correlate with recent reports in hippocampus of subjects with AD and arguably its early form, mild cognitive impairment. Moreover, we show that alterations on HO-1/BVR-A system are tightly connected with cognitive decline indexed by Mini-Mental Status Exam scores. We hypothesize that the HO-1/BVR-A system status in plasma might reflect the ongoing situation in the brain, offering an important biochemical tool for the potential prediction of AD at the earliest stages of the disease.